PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PO. ROSALIA INDAH DI PALUR KARANGANYAR DENGAN FASILITAS SEBAGAI VARIABEL MODERASI - Yosi Pratama (Universitas Slamet Riyadi, 2015)
The purpose of this study is: To analyze the significance of the effect of price, quality of service and facilities to the satisfaction of consumers who use PO bus transportation services. Rosalia Indah in Palur Karanganyar. To analyze the effect of moderating influence of the facility on the price and quality of service to customer satisfaction using bus transportation services PO. Rosalia Indah in Palur Karanganyar. In conclusion: There was a significant effect of price on consumer satisfaction PO bus transport service users. Rosalia Indah in Palur Karanganyar. There was a significant effect of service quality on customer satisfaction PO bus transport service users. Rosalia Indah in Palur Karanganyar. There was a significant influence on consumer satisfaction facility transport service users Bus PO. Rosalia Indah in Palur Karanganyar. Facilities moderate the effect of price on consumer satisfaction PO bus transport service users. Rosalia Indah in Palur Karanganyar. Facilities moderate the impact of service quality on customer satisfaction PO bus transport service users. Rosalia Indah in Palur Karanganyar. Keywords: price, quality of service, facilities and customer satisfaction